Tax law design and drafting - Thuronyi, Victor (Washington, D.C. : International Monetary Fund, 1998)
The book is a work of the IMF in identifying legal issues, providing technical assistance in drafting of tax laws, including those that are often revealed only at the time of their subsequent interpretation and implementation, and the solutions that have been given in national laws
Includes bibliographical references and index.
gp. 22/01/2019
Loans
Keywords: Taxation - law and legislation; Tax administration and procedure; Bill drafting; Tax law; Taxation -government policy